2022
DOI: 10.21037/tcr-22-424
|View full text |Cite
|
Sign up to set email alerts
|

C chemokines are prognostic biomarkers correlated with diverse immune cell infiltrations in clear cell renal cell carcinoma

Abstract: Background: The interplay between tumor-infiltrating immune cells and cancer cells affects cancer initiation, progression, and treatment. C chemokines are critically involved in immune cell chemotaxis, selftolerance formation, antigen cross-presentation, and cytotoxic immune response. However, their roles in cancer development are still largely unknown.Methods: We comprehensively analyzed the expression, prognostic value, functions, and immune implication of C chemokines in clear cell renal cell carcinoma (ccR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The results showed that PPP1R14B expression was negatively correlated with eosinophils, iDCs, mast cells, neutrophils, and other immune cells. Immune cell infiltration can improve the poor prognosis of patients, and low concentrations of infiltrating immune cells can lead to immune escape of cancer cells, resulting in poor prognosis 58,59 . In addition, the results of immune infiltration showed that the degree of Th2 cell infiltration was significantly positively correlated with the expression of PPP1R14B.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that PPP1R14B expression was negatively correlated with eosinophils, iDCs, mast cells, neutrophils, and other immune cells. Immune cell infiltration can improve the poor prognosis of patients, and low concentrations of infiltrating immune cells can lead to immune escape of cancer cells, resulting in poor prognosis 58,59 . In addition, the results of immune infiltration showed that the degree of Th2 cell infiltration was significantly positively correlated with the expression of PPP1R14B.…”
Section: Discussionmentioning
confidence: 99%
“…Immune cell infiltration can improve the poor prognosis of patients, and low concentrations of infiltrating immune cells can lead to immune escape of cancer cells, resulting in poor prognosis. 58,59 In addition, the results of immune infiltration showed that the degree of Th2 cell infiltration was significantly positively correlated with the expression of PPP1R14B. The transition from Th1/Th2 balance to Th2 dominance is a crucial factor in tumour progression, and Th2 cells are not conducive to the antitumour effect of cellular immunity.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between NUDT21 expression and 24 types of immune cells in PAAD showed that NUDT21 expression was negatively correlated with NK cells, pDC, and Th17 cells. Immune cell infiltration improves poor patient prognosis, whereas low concentrations of infiltrating immune cells can lead to immune escape from cancer cells, resulting in poor prognosis (Buisseret et al 2018 ; Chen et al 2020 ). In addition, the results of immune infiltration showed that the degree of Th2 cell infiltration was significantly positively correlated with the expression of NUDT21.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, CXCL13 up-regulation has been shown to correlate with advanced disease stage and poor prognosis ( 71 ). In addition, XCL1 positively correlated with the expression of several inhibitory receptors and cytokines that are associated with T cell exhaustion and several immune checkpoints in ccRCC, thus resulting in a significantly poorer survival ( 72 ). However, as evident from a comparison of concordance indexes of the multi-parameter model consisting of solely clinical and demographic variables and the model including gene expression parameters, there was no add-on value of the investigated chemokine gene expression levels to the prediction accuracy of OS or response to immunotherapy.…”
Section: Discussionmentioning
confidence: 99%